2016
DOI: 10.1038/srep30834
|View full text |Cite
|
Sign up to set email alerts
|

The role of vision for navigation in the crown-of-thorns seastar, Acanthaster planci

Abstract: Coral reefs all over the Indo-Pacific suffer from substantial damage caused by the crown-of-thorns seastar Acanthaster planci, a voracious predator that moves on and between reefs to seek out its coral prey. Chemoreception is thought to guide A. planci. As vision was recently introduced as another sense involved in seastar navigation, we investigated the potential role of vision for navigation in A. planci. We estimated the spatial resolution and visual field of the compound eye using histological sections and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Although much is known of their ecology, much less is known of their sensory biology and how this relates to their interaction with their environment. As has been reported in other starfish species [30, 33, 40] crown-of-thorns starfish have eyes and respond to visual stimulation [34, 35]. Each compound eye has on average 250 eye cups (ommatidia) for animals with a diameter of about 35 cm [34].…”
Section: Introductionmentioning
confidence: 96%
“…Although much is known of their ecology, much less is known of their sensory biology and how this relates to their interaction with their environment. As has been reported in other starfish species [30, 33, 40] crown-of-thorns starfish have eyes and respond to visual stimulation [34, 35]. Each compound eye has on average 250 eye cups (ommatidia) for animals with a diameter of about 35 cm [34].…”
Section: Introductionmentioning
confidence: 96%
“…Suzuki et al [149] reported large numbers of adult CoTS moving across shallow sand flats in Ishigaki Island, southern Japan, which were in very poor condition and ultimately became stranded at low tide. For the most part, adult CoTS in good condition and with reasonable access to coral prey will have limited impetus to move, whereas individuals that are starving are probably unlikely to succeed in traversing large distances between reefs, despite demonstrated capacity for detection of reef structures and selective migration toward coral-rich areas via "vision" or chemoreception [150][151][152][153]. It is very likely that CoTS can and do move between close positioned reefs, especially where there is contiguous reef habitat connecting reefs, but the limited temporal and spatial scales of previous movement studies (as well as the predominant focus on movement within coral habitats) do not really inform the capacity of CoTS to travel large distances between reefs.…”
Section: Question 1 (Adults)-are Adults Capable Of Moving Between Reefs?mentioning
confidence: 99%
“…Crown-of-thorns starfish also regrow damaged or missing arms [28,95], which will require re-allocation of nutrients to regeneration, which could otherwise have been used for immune defence [11], reproduction or somatic growth [88,93]. The removal of arm tips, and consequent removal of the eyespot, may additionally result in reduced foraging efficiency due to the loss of vision, which is important for navigating between reef structures and locating prey [96].…”
Section: Sub-lethal Injuriesmentioning
confidence: 99%